Biscuits, Baking & Cakes : The Essential Recipe Handbook - Edited by Steer, Gina (London Star Fire, 2008)
A guide to baking biscuits, sweet and Savoury items. It shows how to create various things from a French Onion Tart to a Lemony Coconut Cake.
Include Illustration
Keywords: Baking -- Baked products